A Corpus-based Study of Commonly Used Chinese Idioms and Their Pedagogical Design: A Case Study of Thai University Students - Theerapojjanee, Theerawat (Journal of Sinology (วารสารจีนวิทยา), 2008)
Chinese people often apply idioms in writing as the idioms are one of the crucial elements in advanced composition. However, the observation of current phenomena found that both Thai undergraduates and graduates majoring in Chinese are rarely, or never, use Chinese idioms in their writing. This study, therefore, explored possible causes of the problem and sought applicable solutions. Specially designed questionnaires are created to conduct a survey identifying factors that may cause the stated problem. The research extracted 100 Chinese idioms most frequently used from the corpus that was created from five categories’ news reports and articles of Xinhua Online and UDN.COM news websites from March 1st to 31st, 2006, since they are representative of commonly used Chinese idioms in the study. The research compared them with the idioms conducted in Chinese compulsory courses of Chulalongkorn University and Thammasat University which are sample courses of the research. In addition, this paper also analyzed the grammatical functions and semantics of these 100 idioms as the references for Chinese idioms pedagogical design in the final part of the paper.